2016
DOI: 10.1007/s11010-016-2714-1
|View full text |Cite
|
Sign up to set email alerts
|

Globular CTRP9 inhibits oxLDL-induced inflammatory response in RAW 264.7 macrophages via AMPK activation

Abstract: C1q-TNF-related protein-9 (CTRP9) is increasingly recognized as a promising cardioprotective adipocytokine, which regulates biological processes like vascular relaxation, proliferation, apoptosis, and inflammation. We recently showed that CTRP9 enhanced carotid plaque stability by reducing pro-inflammatory cytokines in macrophages. However, the underlying molecular mechanism of CTRP9 on anti-inflammatory response in macrophages still remains unclear. We demonstrated that globular CTRP9 (gCTRP9) significantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…We observed more expression of AdipoR1 than AdipoR2 in BV2 microglia under Aβ induced toxicity. Previous studies demonstrated that downregulation of AdipoR1 attenuates anti-inflammatory responses (Zhang et al, 2016) and reduces the adiponectin’s beneficial actions in macrophages (Luo et al, 2013). We observed that the downregulation of AdipoR1 by siRNA AdipoR1 increases pro-inflammatory cytokines including TNF-α and iNOS production under Aβ toxicity in spite of Acrp30 pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…We observed more expression of AdipoR1 than AdipoR2 in BV2 microglia under Aβ induced toxicity. Previous studies demonstrated that downregulation of AdipoR1 attenuates anti-inflammatory responses (Zhang et al, 2016) and reduces the adiponectin’s beneficial actions in macrophages (Luo et al, 2013). We observed that the downregulation of AdipoR1 by siRNA AdipoR1 increases pro-inflammatory cytokines including TNF-α and iNOS production under Aβ toxicity in spite of Acrp30 pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK activation is responsible for the anti-inflammatory effect of CTRP9 on endothelial cells [17]. Globular CTRP9 alleviates ox-LDL-evoked inflammation in RAW 264.7 macrophages through AMPK activation [35]. Adenovirus-mediated overexpression of CTRP9 activates AMPK to lower serum glucose levels in obese (ob/ob) mice [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies in mice consistently demonstrated the beneficial effects of CTRP9 on vascular endothelial function [14], vascular smooth muscle cell proliferation [13], and the profile of inflammatory cytokines in macrophages [28, 29]. Several studies have investigated the association of CTRP9 with cardiovascular risk factors in human subjects [15, 16, 18], whereas only two reports have shown the association of CTRP9 with atherosclerosis [18] or cardiovascular disease [16].…”
Section: Discussionmentioning
confidence: 99%